A response to G. Aichelle, P. Miscall and R. Walsh, "An Elephant in the room. Historical-critical and the postmodern interpretations of the Bible - Van Seters, John 1935- (2009)
Van Seters's personal response to the recent article by G. Aichele, P. Miscall and R. Walsh, “An Elephant in the Room: Historical-Critical and Postmodern Interpretations of the Bible” (JBL 128 [2009], pp. 383–404) and to the authors's invitation for a conversation among historical-critical and postmodern biblical scholars.